The Memory Alteration Test Is Correlated with Clinical, Cerebrospinal Fluid, and Brain Imaging Markers of Alzheimer Disease in Lima, Peru - Custodio, N (2024)
Introduction: As disease-modifying therapies become available for Alzheimer’s disease (AD), detection of AD in early stages of illness (mild cognitive impairment [MCI], early dementia) becomes increasingly important. Biomarkers for AD in low- and middle-income countries (LMICs) are costly and not widely available; hence, it is important to identify cognitive tests that correlate well with AD biomarker status. In this study, we evaluated the memory alteration test (M@T) to detect biomarker-proven AD and quantify its correlation with neurodegeneration and cerebrospinal fluid (CSF) AD biomarkers in a cohort of participants from Lima, Peru. Methods: This is a secondary analysis of a cohort of 185 participants: 63 controls, 53 with amnestic MCI (aMCI), and 69 with dementia due to AD. Participants underwent testing with M@T and a gold standard neuropsychological battery. We measured total tau (t-tau), phosphorylated tau (p-tau), and beta-amyloid (β-amyloid) in CSF, and evaluated neurodegeneration via medial temporal atrophy score in MRI. We used receiver-operator curves to determine the discriminative capacity of the total M@T score and its subdomains. We used the Pearson coefficient to correlate M@T score and CSF biomarkers. Results: The M@T had an area under the curve (AUC) of 0.994 to discriminate between controls and cognitively impaired (aMCI or AD) patients, and an AUC of 0.98 to differentiate between aMCI and AD patients. Free-recall and cued recall had the highest AUCs of all subdomains. Total score was strongly correlated with t-tau (−0.77) and p-tau (−0.72), and moderately correlated with β-amyloid (0.66). The AUC for discrimination of neurodegeneration was 0.87. Conclusion: The M@T had excellent discrimination of aMCI and dementia due to AD. It was strongly correlated with CSF biomarkers and had good discrimination of neurodegeneration. In LMICs, the M@T may be a cost-effective screening tool for aMCI and dementia caused by AD.